Biosimilars in the French and Polish System: Chosen Aspects of Reimbursement and Access - Olga Barszczewska; Ralph Chami; Anna Piechota (Comparative Economic Research. Central and Eastern Europe, 2020)
The EU approved the first biosimilar drug in 2006. By 2017, the EU had authorized the highest number of biosimilars worldwide, acquiring considerable experience in their use and safety. In May 2019, the European Medicines Agency (EMA) search engine showed 54 authorized biosimilars. Biosimilars reduce public expenditure; however, the discussion about their potential disadvantages is still ongoing. Each country adopts different regulations on the interchangeability, switching, and substitution of a reference medicine by its biosimilar, since the EMA does not regulate this issue. Additionally, each nation has a unique reimbursement system, which results in significant differences in patients' access to biosimilars. The importance of securing a higher availability of these cheaper versions of biological drugs is well-recognized. The better the access to these biosimilars is, the lower the overall drug expenditure and need for rationing would be, and therefore the better treatment results. The aim of this paper is to compare selected aspects of reimbursement and access to the EMA authorized biosimilar medicines in two countries - France and Poland. The stated drug policy goal of both countries is to significantly improve biosimilar implementation in the coming years. The research is based on an analysis of four main sources: the EMA biosimilars database, the Polish reimbursement list published by the Polish Ministry of Health, and two French reimbursement databases published by the French Ministry of Health. An additional literature review was conducted. The expected results concentrate on differences in the number of reimbursed biosimilars, the average time between EMA authorization and country reimbursement decision date, and the availability of biosimilars registered outside of the centralized (EMA) procedure. These findings could identify areas of improvement and help with discussions on how to optimize the reach of biosimilars, as well as improve French-Polish collaboration on this matter.
Keywords: H51; H75; I15; I18; 330; biosimilars; biosimilar medicines; healthcare system; reimbursement; access; EMA; Ministry of Health